(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This research aims to determine the correlation between self-confidence and news text speaking skills of eleventh-grade students at SMA Koperasi Pontianak. This study used a quantitative method with a correlation research design. The population and sample of this study were eleventh-grade students at SMA Koperasi Pontianak. Data collection was carried out through a questionnaire instrument to measure self-confidence and a performance assessment rubric to measure news text speaking skills. The data analysis technique used was the Product Moment correlation analysis. The results showed that the students’ self-confidence level was in the fairly good category (mean 70.94) and the speaking skill level was also in the fairly good category (mean 71.11). Based on the analysis, a very strong and significant positive correlation was found between self-confidence and news text speaking skills. This finding is evidenced by a correlation coefficient value of 0.911, which is greater than the r-table value of 0.388, indicating that the research hypothesis is accepted.